Thyroid Function in Molar Pregnancies - Sinha, Kavita; Das, Ram; Adhikari, Homnath (Journal of Nepalgunj Medical College, 2022)
Introduction: Molar pregnancies represent a significant burden of disease on the spectrum of gestational trophoblastic diseases. Vaginal bleeding being the most common occasionally, molar pregnancy is complicated by hyperthyroidism, which may require treatment.Aims: To determine thyroid function test and association of hyperthyroidism among the cases of molar pregnancy.Methods: This is a hospital-based cross-sectional study conducted in the department of Obstetrics and Gynecology, Nepalgunj Medical College and Teaching Hospital, Kohalpur. Sixty cases of molar pregnancy were included during the study period from February 2020 to January 2021.Patients having history of known thyroid disorders were excluded.Results: Prevalence of molar pregnancy in our study was 5.4 per thousand pregnancies in our hospital. Molar pregnancy and hyperthyroidism, both were common in the age group of 21-35 years. Hyperthyroidism was present in 10% patients. Enlarged thyroid was seen in 3.3%, tremor was present in 3.3%, and palpitation in 21.5%. Five (8.3%) patients with hyperthyroidism were underweight. Majority of patients with hyperthyroidism, beta humanchorionic gonadotrophhin level was more than three lakhs and it was mostly associated with complete hydatidiform mole compared to partial hydatidiform mole. Thyroid storm was not experienced in any of the patients.Conclusion: The rate of molar pregnancy is high. Hyperthyroidism in molar pregnancy is not uncommon. High levels of human chorionic gonadotropin, complete hydatiform mole are directly associated with hyperthyroidism. Awareness of this condition is important for diagnosis and treatment to prevent life threatening complications.